Probiotic Microencapsulation To Improve The Physical Quality Of Goat Milk Set Yogurt - Archadiya, Meilan; Rahmawati, Dewi; Anshari, Olpha Agustin Putri (Syntax Literate, 2026)
Goat milk yogurt is valued for its nutritional benefits but often faces challenges such as low viscosity, high syneresis, and poor water retention. Probiotic microencapsulation offers a promising approach to enhance bacterial viability and improve product quality during fermentation. This research aimed to determine the effect of concentrations of encapsulated Lactobacillus bulgaricus FNCC 0035 and Streptococcus thermophilus FNCC 0040 on the physical quality (viscosity, syneresis, WHC, colour L*, a*, b*) of goat milk set yogurt. The research method used was a laboratory experiment with a completely randomized design (CRD) consisting of four treatments: T0 (addition of 2% LAB starter without encapsulation), T1 (addition of 2% encapsulated LAB starter), T2 (addition of 3% encapsulated LAB starter), and T3 (addition of 4% encapsulated LAB starter), with three replications. Data were analyzed using analysis of variance (ANOVA); if a significant effect was found, further testing was carried out using Duncan's Multiple Range Test (DMRT). The analysis of variance showed that the addition of encapsulated Lactobacillus bulgaricus FNCC 0035 and Streptococcus thermophilus FNCC 0040 had a significant effect (P < 0.05) on the physical characteristics of goat's milk set yogurt. The best treatment was T3, with average viscosity of 1180 cP, syneresis of 7.8%, WHC of 77.8%, L* colour value of 83.1, a* of −1.55, and b* of 11.0. These findings indicate that microencapsulation effectively enhances the physical quality of goat milk yogurt, supporting its potential as a value-added functional food product.